2018
DOI: 10.1111/jpet.12288
|View full text |Cite
|
Sign up to set email alerts
|

Trade, environment, and income inequality: An optimal taxation approach

Abstract: In a small open economy, how should a government pursuing both environmental and redistributive objectives design domestic taxes when redistribution is costly? And how does trade liberalization affect the economy's levels of pollution and inequalities, when taxes are optimally and endogenously adjusted? Using a general equilibrium model under asymmetric information with two goods, two factors (skilled and unskilled labor) and pollution, this paper characterizes the optimal mixed tax system (nonlinear income ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Environmental pollution can accelerate the depreciation of individual health [31,32]. The rich's willingness and ability to pay for a clean environment are higher while the poor are always exposed to areas with a high concentration of pollution, indicating that environmental inequalities could lead to health inequalities [33][34][35][36]. The effect of foreign trade on environmental pollution depends on the net effect of scale effect, structure effect, and technology effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental pollution can accelerate the depreciation of individual health [31,32]. The rich's willingness and ability to pay for a clean environment are higher while the poor are always exposed to areas with a high concentration of pollution, indicating that environmental inequalities could lead to health inequalities [33][34][35][36]. The effect of foreign trade on environmental pollution depends on the net effect of scale effect, structure effect, and technology effect.…”
Section: Introductionmentioning
confidence: 99%
“…Structure effect is ambiguous depending on whether international trade transfers green industrial structure [37][38][39][40]. The differences in these three effects of foreign trade among provinces can contribute to environmental inequalities [35,41,42]. Richardson et al (2013) [34] found that the free trade between eastern and western counties deteriorated the environment in less-developed western counties, leading to Europe-wide mortality inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the distributional effect of public R&D investment has received little attention. In the extant literature, the focus is more on public education (e.g., Benabou, ; Glomm & Ravikumar, ), globalization (e.g., Bontems & Gozlan, ) and infrastructure and taxes (e.g., Alesina & Rodrik, ; Chatterjee & Turnovsky, ; Garcia‐Penalosa & Turnovsky, ; Getachew, ; Getachew & Turnovsky, ). R&D investment could have uneven impacts on the economy and, through this channel, could impact rich and poor differently.…”
Section: Introductionmentioning
confidence: 99%
“…They show that depending on the marginal disutility of pollution, the regions will compete by either undercutting or increasing their tax rates. In a small open economy setting, Bontems and Gozlan () analyze the trade‐off between environmental and redistributive goals within an optimal taxation model. They derive conditions under which it is optimal to either underinternalize or overinternalize social marginal damage for redistributive considerations.…”
Section: Introductionmentioning
confidence: 99%